Chronic stress promotes colitis by disturbing the gut microbiota and triggering immune system response - Gao, Xinghua (Proc Natl Acad Sci U S A, 2018)
Chronic stress is known to promote inflammatory bowel disease (IBD), but the underlying mechanism remains largely unresolved. Here, we found chronic stress to sensitize mice to dextran sulfate sodium (DSS)-induced colitis; to increase the infiltration of B cells, neutrophils, and proinflammatory ly6C(hi) macrophages in colonic lamina propria; and to present with decreased thymus and mesenteric lymph node (MLN) coefficients. Circulating total white blood cells were significantly increased after stress, and the proportion of MLN-associated immune cells were largely changed. Results showed a marked activation of IL-6/STAT3 signaling by stress. The detrimental action of stress was not terminated in IL-6(−/−) mice. Interestingly, the composition of gut microbiota was dramatically changed after stress, with expansion of inflammation-promoting bacteria. Furthermore, results showed stress-induced deficient expression of mucin-2 and lysozyme, which may contribute to the disorder of gut microbiota. Of note is that, in the case of cohousing, the stress-induced immune reaction and decreased body weight were abrogated, and transferred gut microbiota from stressed mice to control mice was sufficient to facilitate DSS-induced colitis. The important role of gut microbiota was further reinforced by broad-spectrum antibiotic treatment. Taken together, our results reveal that chronic stress disturbs gut microbiota, triggering immune system response and facilitating DSS-induced colitis.